Design and Construction Control of Warm Mix Epoxy Asphalt Mixture with Low Epoxy Content for Service Area Pavements - Bo Chen; Kai Chen; Xuetang Xiong; Yi Deng; Zicong Chen; Weixiong Li; Huayang Yu (Buildings)
Highway service area pavements are exposed to severe conditions such as heavy traffic, oil infiltration, and temperature fluctuations, which lead to issues like rutting and cracking in conventional asphalt mixtures. Although warm mix epoxy asphalt mixtures have high strength and corrosion resistance, their high epoxy content and stringent construction requirements limit their engineering applications. To address these challenges, a design and construction method for warm mix epoxy asphalt mixtures with low epoxy content (≤20%) was proposed. The mineral aggregate gradation was optimized using the CAVF volumetric method, and the impact of different epoxy asphalt-aggregate ratios was analyzed through various performance tests, including Marshall stability, high-temperature stability, low-temperature bending, and oil resistance tests. The construction available time was determined using viscosity tests, and process parameters were optimized based on infrared thermography and real-time compaction monitoring. The results show that a 5.4% epoxy asphalt-aggregate ratio yields the best overall performance, with significantly better dynamic stability, tensile strain, and oil resistance compared to SBS-modified asphalt mixtures. The recommended construction parameters, including temperature control and compaction process, ensure optimal performance and durability. The proposed methods provide essential technical support for the effective application of warm mix epoxy asphalt in service area pavements.